Needs Analysis Model Construction for the Advanced Level of HSK - Xiaoshan, Mo; Mengyu, Chen; Lian, Luo (Sinología hispánica. China Studies Review, 2024)
The test users of Chinese Proficiency Test (Hanyu Shuiping Kaoshi, hereinafter referred to as HSK) have been becoming more and more diverse, and it is high time for the concerning authorities to investigate the test users’ needs and launch a new advanced HSK test. Therefore, this paper first reviews the relevant studies of foreign language needs analysis models, and presents the significance to establish a needs analysis model for HSK. Based on Dudley-Evans & St John's needs analysis model and Knoch, U. & Macqueen, S.'s needs analysis model, the paper proposes a theoretical framework of the needs analysis model of HSK (advanced) that consists seven perspectives: personal information, language information and professional information, gap of Chinese language learners, satisfaction with the existing HSK, expectations for HSK (advanced), needs for test resources, and the impact of relevant policies on the test. It also introduces the information sources, information collection methods and possible questions, in order to provide reference for the development of HSK (advanced).